2000
DOI: 10.1046/j.1364-3703.2000.00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas syringae pv. tomato: the right pathogen, of the right plant, at the right time

Abstract: Pseudomonas syringae pv. tomato and the closely related pathovar P. s. pv. maculicola have been the focus of intensive research in recent years, not only because of the diseases they cause on tomato and crucifers, but because strains such as P. s. pv. tomato DC3000 and P. s. pv. maculicola ES4326 are pathogens of the model plant Arabidopsis thaliana . Consequently, both P. s. pv. tomato and P. s. pv. maculicola have been widely used to study the molecular mechanisms of host responses to infection. Analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(135 citation statements)
references
References 105 publications
1
130
0
4
Order By: Relevance
“…Approximately 5% of the P. syringae DC3000 genes encode for proteins involved in virulence (Rahme et al, 1995;Preston, 2000;Buell et al, 2003). Many of these proteins function in bacterial mobility, the nutrient transport system, reactive oxygen species detoxification, or biosynthesis of the bacterial polysaccharide capsule (Buell et al, 2003 , redox-related proteins (glutathione S-transferases, superoxide dismutases, thioredoxin, catalase), and flagellin.…”
Section: Application Of Cpll To Protein Extracts From Infected Leavesmentioning
confidence: 99%
“…Approximately 5% of the P. syringae DC3000 genes encode for proteins involved in virulence (Rahme et al, 1995;Preston, 2000;Buell et al, 2003). Many of these proteins function in bacterial mobility, the nutrient transport system, reactive oxygen species detoxification, or biosynthesis of the bacterial polysaccharide capsule (Buell et al, 2003 , redox-related proteins (glutathione S-transferases, superoxide dismutases, thioredoxin, catalase), and flagellin.…”
Section: Application Of Cpll To Protein Extracts From Infected Leavesmentioning
confidence: 99%
“…tomato DC3000 (Pst; Preston, 2000) was obtained from Dr N. Schlaich, RWTH Aachen, Germany. Pst was grown on liquid King's B medium (King et al, 1954) supplemented with 50 μg ml − 1 rifampicin and 50 μg ml − 1 kanamycin overnight at 28°C.…”
Section: Plant Infection With Pseudomonasmentioning
confidence: 99%
“…Pseudomonas syringae is a gram-negative plant pathogen that causes a wide variety of diseases, including blights, leaf spots, and galls, in different plant species and is a model system in molecular plant pathology (Preston, 2000). Sequencing and genetic studies have identified many key pathogenicity and virulence determinants in P. syringae, including global virulence regulators, the type III secretion system, phytotoxins, and exopolysaccharides (Buell et al, 2003).…”
mentioning
confidence: 99%